A high-precision age estimate of the Holocene Plinian eruption of Mount Mazama, Oregon, USA. (July 2015) - Egan, Joanne; Staff, Richard; Blackford, Jeff
The climactic eruption of Mount Mazama in Oregon, North America, resulted in the deposition of the most widespread Holocene tephra deposit in the conterminous United States and south-western Canada. The tephra forms an isochronous marker horizon for palaeoenvironmental, sedimentary and archaeological reconstructions, despite the current lack of a precise age estimate for the source eruption. Previous radiocarbon age estimates for the eruption have varied, and Greenland ice-core ages are in disagreement. For the Mazama tephra to be fully utilised in tephrochronology and palaeoenvironmental research, a refined (precise and accurate) age for the eruption is required. Here, we apply a meta-analysis of all previously published radiocarbon age estimations ( n = 81), and perform Bayesian statistical modelling to this data set, to provide a refined age of 7682–7584 cal. yr BP (95.4% probability range). Although the depositional histories of the published ages vary, this estimate is consistent with that estimated from the GISP2 ice-core of 7627 ± 150 yr BP (Zdanowicz et al., 1999).